Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.7150/jca.41492
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-129-2-3p directly targets Wip1 to suppress the proliferation and invasion of intrahepatic cholangiocarcinoma

Abstract: Accumulated studies showed that numerous microRNAs (miRNAs) were aberrantly expressed in human intrahepatic cholangiocarcinoma (ICC) and contributed to the tumorigenic processes. However, whether miR-129-2-3p is implicated in the ICC initiation and progression is still limited. Here, the results revealed that miR-129-2-3p expression was notably decreased in ICC tissues and cell lines, and that a low miR-129-2-3p expression was obviously associated with distant metastasis and clinical stage. Exogenous miR-129-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“… 19 The only potentially curative treatment for ICC is radical surgery. 6 , 7 , 20 However, less than 30% of patients undergo surgical resection because the early diagnosis rate of ICC is very low. Moreover, the 5-year survival rate after ICC surgical resection is less than 45%, and the recurrence rate is about 50% from most clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 19 The only potentially curative treatment for ICC is radical surgery. 6 , 7 , 20 However, less than 30% of patients undergo surgical resection because the early diagnosis rate of ICC is very low. Moreover, the 5-year survival rate after ICC surgical resection is less than 45%, and the recurrence rate is about 50% from most clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Therefore, it has important clinical significance for finding new prognostic indicators and therapeutic targets by exploring the molecular mechanism of the progression of ICC. [5][6][7] MicroRNAs (miRNAs) are highly conserved small noncoding RNAs, with lengths of approximately 17-25 nucleotides. Recently, miRNAs have been shown to be involved in multiple steps that regulate the occurrence and development of ICC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of mir-129-2-3p was significantly decreased in EWS tumor samples, and this downregulation was more obvious in Enneking IIB patients. The tumor suppressor effect of mir-129-2-3p was shown in ovarian cancer [13], cholangiocarcinoma [14], gastric cancer [15], glial and glioneuronal tumors [16]. It was found that mir-129-3p is suppressed by DNA hypermethylation in primary gastric cancers, and its decreased expression level is associated with the clinical and pathological characteristics of individuals with gastric cancer [17].…”
Section: Discussionmentioning
confidence: 99%
“…The Notch signaling pathway, which is highly conservative in evolution, participates in the regulation of a variety of malignant biological behaviors of tumor cells, and plays an important role in the process of CCA biogenesis. Liu et al [64] found that the expression of miR-129-2-3p in ICCA tissues and cells was reduced, and its target gene Wip1 played a tumor-suppressing effect in the progression of ICCA. The high level of Wip1 in human ICCA is associated with metastasis to lymph nodes (P=0.022).…”
Section: Extrahepaticmentioning
confidence: 99%